Isabella Abnormella and the very, very finicky Queen of Trouble - Lewis, J. Patrick (DK Pub., 2000)
When the Queen of Trouble cannot sleep because all the beds she tries are uncomfortable, Isabella Abnormella saves the day by inventing the waterbed.